N-3 PUFA increase bioavailability and function of endothelial progenitor cells - Spigoni, Valentina; Lombardi, Carlo; Cito, Monia; Picconi, Angela; Ridolfi, Valentina; Andreoli, Roberta; Anelli, Nadia; Gnudi, Luigi; Goldoni, Matteo; Zavaroni, Ivana; Raddino, Riccardo; Cas, Alessandra Dei (Food & function, 2014)
Recent data suggest that n-3 PUFA exert beneficial effects on endothelial progenitor cell (EPC) biology. We sought to investigate whether these effects might be mediated by enhanced EPC in vitro function and/or in vivo bioavailability. CACs and late-outgrowth EPCs were isolated from peripheral blood mononuclear cells obtained from 12 donor buffy-coats. The effect of n-3 PUFA (EPA:DHA = 0.9:1.5; 9 μM EPA plus 15 μM DHA) was tested on CAC/EPC viability, function (tube-formation) and pro-inflammatory molecule expression. Circulating EPC (cells positive for CD34, CD133 and kinase insert domain receptor - KDR cell-surface antigens by flow cytometry) number was evaluated in 20 healthy subjects (10 F/10 M, 32 ± 5 years), randomized to receive 4 mackerel or sardine portions per week for 6 weeks followed by a 6 week free-diet period. N-3 PUFA improved CAC and late-outgrowth EPC viability (p < 0.05) and the capacity to form tube-like structures in CACs (+38%; p < 0.05) and late-outgrowth EPCs (+15%; p < 0.05). ICAM-1 expression was reduced in both CACs (p < 0.05) and late-outgrowth EPCs (p < 0.05) and VCAM-1 in late-outgrowth EPCs (p < 0.005). N-3 PUFA significantly decreased TNF-α and MCP-1 expression in CACs and IL-8, TNF-α and MCP-1 in late-outgrowth EPCs (p < 0.05). Circulating EPC number significantly improved after 6 weeks of a fish-enriched diet (p < 0.01) and returned to baseline levels after a 6 week free-diet period (p < 0.01). Plasma EPA levels were independently and positively associated with EPC levels (p < 0.005). Our findings support the case of a beneficiary role played by n-3 PUFA in EPC function and bioavailability.